PENGARUH PENERAPAN BALANCED SCORECARD TERHADAP KINERJA MANAJEMEN PADA PT XYZ - Joni Efendi (JURNAL MITRA MANAJEMEN, 2023)
This research is about PT XYZ's management performance appraisal from four balance scorecard performance perspectives. This type of research is a causal comparison with qualitative analysis which is strengthened by using a Likert scale. The results of the research were processed using SPSS version 23 with partial analysis showing that there is a significant influence between the Financial Perspective and Management Performance. By 28.4%, there is a significant influence between Internal Business Processes and Management Performance. By 29.4%, there is a significant influence between the Learning and Growth Perspective and Management Performance of 37.9%. There is no significant influence between Customer Perspective and Management Performance with a correlation coefficient of 3.6%. Analysis of simultaneous results between the Financial Perspective, Customer Perspective, Internal Business Process Perspective and Learning Perspective, and Growth with Management Performance with a regression value of 6,690 which means that if the four independent variables are constant, then the application of the balanced scorecard to Management Performance is 6,690. The value of the coefficient of determination of Management Performance can be explained by the variables of financial perspective, customers, internal business processes and learning and growth. by 52.7%. Keywords: Balance Scorecard, Performance Management